Stage-specific prevalence and progression of sarcopenia among aging hemodialysis patients: a multicenter cross-sectional study - Li, Jinguo; Wang, Fei; Song, Lili; Fang, Fang; Shen, Mengru; Wang, Hongyu (Frontiers in Public Health, 2025)
ObjectivesTo investigate the stage-specific prevalence and progression mechanisms of sarcopenia in aging patients undergoing maintenance hemodialysis (MHD), and to identify modifiable risk and protective factors relevant to early public health interventions.MethodsThis multicenter cross-sectional study enrolled 448 eligible older adults (aged ≧ 60 years) undergoing maintenance hemodialysis (MHD) from three tertiary hospitals in Bengbu, China, between January and April 2025, using convenience sampling. Sarcopenia was classified according to the Asian Working Group for Sarcopenia (AWGS) 2019 criteria. Data on demographics, body composition, nutrition, self-efficacy, physical activity, and inflammation were collected. Logistic regression analyses identified factors associated with sarcopenia onset and progression.ResultsSarcopenia prevalence was 54.0%, with 25.0% at the possible stage, 19.6% confirmed, and 9.4% severe. Key protective factors for sarcopenia onset included female sex, higher basal metabolic rate (BMR), higher Body Mass Index (BMI) and greater self-efficacy (SES6). Risk factors included low physical activity, diabetes, longer dialysis vintage, and malnutrition (MQSGA). Progression to confirmed/severe stages was independently associated with reduced BMI, protein mass, and self-efficacy, along with elevated BMR and physical inactivity. These findings highlight the importance of early screening and personalized preventive strategies in aging MHD populations.ConclusionSarcopenia is highly prevalent among older adults receiving MHD, with distinct stage-specific progression patterns. This study identified key modifiable risk and protective factors related to both the onset and progression of sarcopenia. Early detection of possible sarcopenia and timely interventions targeting nutrition, physical activity, and self-efficacy may delay progression and promote healthy aging in this population.